Dieter Henrich’s Early Approach to the Transcendental Deduction of the Categories - Rettweiler, Frank (Studia Kantiana, 2023)
The anxious over-reaction against psychologism hast still shaped Dieter Henrich's early interpretation of the proof-structure of the transcendental deduction of the second edition of the Critique of Pure Reason. From this over-reaction against psychologism, the role of the concept of synthesis and the role it plays in the transcendental deduction of categories is underestimated. This underestimation of the concept of synthesis obscures the proof structure of the transcendental deduction.